Organizational Health and Employer Brand Attractiveness - Chehrehgosha, Arezoo; Teimouri, Dr. Hadi (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aimed to determine the relationship between organizational health and employer brand attractiveness in FANAP Company. The statistical population of the study consisted of all the managers and experts of Pasargad Arian Information and Communication Technology Company (FANAP), and 325 of them were selected by Stratified random sampling method. The validity of the questionnaire was confirmed by academic experts as well as experts from FANAP Company. Also, with the use of Cronbach’s alpha coefficient, the reliability of the questionnaire was calculated to be 0.86 which indicates the reliability of the questionnaire. The hypotheses were examined using SPSS software at the descriptive level with frequency descriptive statistics and frequency percentage and using Amos software at the inferential level. According to the results of this study, there is a significant relationship between organizational health and employer brand attractiveness.